2017
DOI: 10.1111/psyp.12845
|View full text |Cite
|
Sign up to set email alerts
|

Consequences matter: Self‐induced tones are used as feedback to optimize tone‐eliciting actions

Abstract: Experimental paradigms investigating the processing of self-induced stimuli are often based on the implicit assumption that motor processes are invariable regardless of their consequences: It is presumed that actions with different sets of predictable sensory consequences do not differ in their physical characteristics or in their brain signal reflections. The present experiment explored this assumption in the context of action-related auditory attenuation by comparing actions (pinches) with and without audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 66 publications
(78 reference statements)
3
40
0
Order By: Relevance
“…Finally, the current protocol did not require participants to make an active movement to signal the onset of their inner phoneme, such as by pressing a button. This is a significant advantage over previous studies which have employed a motor condition to signal the onset of covert actions, as it avoids the potential confound associated with having temporally-overlapping auditory-evoked and motor-evoked potentials – see Horvath ( Horváth, 2015 ) and Neszmélyi and Horvath ( Neszmélyi and Horváth, 2017 ) for a discussion of the challenges associated with ‘correcting’ for motor activity in studies of sensory attenuation. In light of its methodological features, the present study provides arguably the strongest evidence to date that inner speech results in sensory attenuation of the N1-component of the auditory-evoked potential, even in the absence of an overt motor response.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the current protocol did not require participants to make an active movement to signal the onset of their inner phoneme, such as by pressing a button. This is a significant advantage over previous studies which have employed a motor condition to signal the onset of covert actions, as it avoids the potential confound associated with having temporally-overlapping auditory-evoked and motor-evoked potentials – see Horvath ( Horváth, 2015 ) and Neszmélyi and Horvath ( Neszmélyi and Horváth, 2017 ) for a discussion of the challenges associated with ‘correcting’ for motor activity in studies of sensory attenuation. In light of its methodological features, the present study provides arguably the strongest evidence to date that inner speech results in sensory attenuation of the N1-component of the auditory-evoked potential, even in the absence of an overt motor response.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies on sensory attenuation in EEG/MEG activity have implemented a motor control condition in which a motor act is performed without stimulus presentation (e.g., [ 2 , 18 , 19 ]). The evoked response in the motor control condition is then subtracted from the auditory-evoked responses with self-generated sounds to correct for any potential motor contamination in the auditory-evoked responses due to the motor act preceding the stimulus presentation (however, see [ 48 ] for negative evidence of the effectiveness of this strategy). We did not include such a control condition to avoid making the study excessively long, because of the focus of our study on adaptation (see also [ 49 , 50 ] for examples of other MEG sensory attenuation studies not using such a control condition).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with response-effect compatibility paradigms, the present study utilized a single action category, that is, there were no alternative response options; and measured the motor parameters of the actions within that single action category. The notion that motor parameters within a single category of actions may change even in the absence of an alternative action category, as a function of the elicited effects, is supported by a recent study by Neszmélyi, & Horváth 15 , in which actions with and without auditory consequences (in separate experimental blocks) were compared. It was found that participants applied less force when actions elicited a sound ( action-effect related force adaptation ).…”
Section: Introductionmentioning
confidence: 91%
“…That is, pinching may not have the tactile effects that define successful interactions with most everyday devices, thus may not allow participants to encode pinching in “tactile terms” as, for example, button presses may do. Therefore, one may argue that the action-effect related force adaptation reported by Neszmélyi and Horváth 15 was specific to pinching, and may not reflect a general phenomenon. The goals of the three experiments of the present study were to replicate the original results (Pinch Experiment), and to test whether action-effect related adaptation could also be observed for more frequently used types of interactions: tapping (Tap Experiment) and button pressing (Button Experiment).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation